THE DETERMINANTS OF USING VASECTOMY CONTRACEPTION IN SOMBA OPU DISTRICT, INDONESIA - Raodhah, Sitti; Kasriana, Kasriana (Homes Journal: Hospital Management Studies Journal, 2020)
Background: MOP (Male Operation Method) is an alternative family planning method for men who have decided they don’t want to have more children by undergoing minor surgery on the sperm duct by blocking or blocking the way for the sperm to prevent fertilization. Objective: The purpose of this study was to determine the determinants of the use of MOP (Male Operation Method) / Vasectomy contraception in Somba Opu District, Gowa Regency. Method: This research is quantitative research with analytics method by using cross sectional study,The sampling technique used was proportional random sampling with a sample size of99 respondents. The data collection employed was a questionnaire, and the data was analyzed using the chi-square test. Result: The results showed that there was an influence between income (p = 0.002), knowledge (p = 0.003), attitude (p = 0.004), wife’s support (p = 0.004) with the use of MOP contraception and there was no influence between age (p = 0.082), education (p = 0.465), the number of children (p = 0.204), the number of children wanted (p = 0.876), PLKB (p = 0.267) with the use of MOP contraception. Conclusion: This study is expected to gain a clear understanding of contraceptives and can easily determine their choice of family planning, especially male FP (Male Operation Method).